2016
DOI: 10.11138/fneur/2016.31.3.127
|View full text |Cite
|
Sign up to set email alerts
|

Women with epilepsy: clinically relevant issues

Abstract: SummaryWomen with epilepsy (WWE) face specific challenges throughout their lifespan due to the effects of seizures and antiepileptic drugs on hormonal function, potentially affecting both sexual and reproductive health. This review article addresses the most common issues of practical relevance to clinicians treating WWE: epidemiology and clinical presentations (including catamenial epilepsy), contraception, reproductive and sexual dysfunction, pregnancy, lactation, menopause-related issues (including bone hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 77 publications
1
28
0
Order By: Relevance
“…The relationship between menstrual parameters and AED in the study will suggest carbamazepine may act at this level. Carbamazepine has been shown to impact on FSH level, as it aids conversion of inactive to active metabolite (Bangar et al2016, Svalheim et al, 2009, Verrotti et al, 2011 The fact that an ovulatory condition like polycystic ovarian syndrome is less common with carbamazepine contrary to the use of other anti-epileptic drugs that reduces the FSH level also supports this notion (Bangar et al, 2016;Svalheim et a l., 2009, Verrotti et al 2011. It is therefore explainable that values of LH/FSH among WWE not on carbamazepine were greater than 1 in our study.…”
Section: Discussionmentioning
confidence: 98%
“…The relationship between menstrual parameters and AED in the study will suggest carbamazepine may act at this level. Carbamazepine has been shown to impact on FSH level, as it aids conversion of inactive to active metabolite (Bangar et al2016, Svalheim et al, 2009, Verrotti et al, 2011 The fact that an ovulatory condition like polycystic ovarian syndrome is less common with carbamazepine contrary to the use of other anti-epileptic drugs that reduces the FSH level also supports this notion (Bangar et al, 2016;Svalheim et a l., 2009, Verrotti et al 2011. It is therefore explainable that values of LH/FSH among WWE not on carbamazepine were greater than 1 in our study.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies including the International Registry of Antiepileptic Drugs and Pregnancy (EURAP) study found that the prepregnancy seizure baseline was the largest predictor of seizures during pregnancy itself, with 60% of women remaining seizure-free throughout their pregnancy. [39][40][41][42][43] EURAP also found that women with epilepsy did not have an increased risk of seizures during the second or third trimesters compared to their first trimester baseline. Likewise, a 7-year study of 841 women with epilepsy being treated with antiseizure drugs based on the Australian Register of Antiepileptic Drugs in Pregnancy found that a period of seizure freedom lasting at least 1 year prior to pregnancy was associated with a 50%-70% reduction in risk of seizures during pregnancy, as well as reduced risk of seizures in the first postpartum month.…”
Section: Discussionmentioning
confidence: 99%
“…In general, newer AEDs have a safer risk profile to the unborn child. 28 Preconception folic acid can lessen the risk, particularly of neural tube defects. As such, all WWE of child-bearing age should receive preconception folic acid supplementation.…”
Section: Women's Issuesmentioning
confidence: 99%